Poly(L-lysine)-modified iron oxide nanoparticles for stem cell labeling - Babic, Michal; Horák, Daniel; Trchová, Miroslava; Jendelová, Pavla; Glogarová, Katerina; Lesný, Petr; Herynek, Vít; Hájek, Milan; Syková, Eva (Bioconjugate chemistry, 2008)
New surface-modified iron oxide nanoparticles were developed by precipitation of Fe(II) and Fe(III) salts with ammonium hydroxide and oxidation of the resulting magnetite with sodium hypochlorite, followed by the addition of poly( L-lysine) (PLL) solution. PLL of several molecular weights ranging from 146 ( L-lysine) to 579 000 was tested as a coating to boost the intracellular uptake of the nanoparticles. The nanoparticles were characterized by TEM, dynamic light scattering, FTIR, and ultrasonic spectrometry. TEM revealed that the particles were ca. 6 nm in diameter, while FTIR showed that their surfaces were well-coated with PLL. The interaction of PLL-modified iron oxide nanoparticles with DMEM culture medium was verified by UV-vis spectroscopy. Rat bone marrow stromal cells (rMSCs) and human mesenchymal stem cells (hMSC) were labeled with PLL-modified iron oxide nanoparticles or with Endorem (control). Optical microscopy and TEM confirmed the presence of PLL-modified iron oxide nanoparticles inside the cells. Cellular uptake was very high (more than 92%) for PLL-modified nanoparticles that were coated with PLL (molecular weight 388 00) at a concentration of 0.02 mg PLL per milliliter of colloid. The cellular uptake of PLL-modified iron oxide was facilitated by its interaction with the negatively charged cell surface and subsequent endosomolytic uptake. The relaxivity of rMSCs labeled with PLL-modified iron oxide and the amount of iron in the cells were determined. PLL-modified iron oxide-labeled rMSCs were imaged in vitro and in vivo after intracerebral grafting into the contralateral hemisphere of the adult rat brain. The implanted cells were visible on magnetic resonance (MR) images as a hypointense area at the injection site and in the lesion. In comparison with Endorem, nanoparticles modified with PLL of an optimum molecular weight demonstrated a higher efficiency of intracellular uptake by MSC cells.
Keywords: Stem Cell Transplantation; Animals; Microscopy, Electron, Transmission; Chemistry, Physical; Lysine; Magnetic Resonance Imaging; lysin; velikost částic; oxidy; mezenchymální kmenové buňky; železo; Ultrasonics; Microscopy, Electron, Scanning; Oxides; Particle Size; Adsorption; Nanoparticles; železité sloučeniny; lidé; mikroskopie elektronová rastrovací; transplantace kmenových buněk; Spectroscopy, Fourier Transform Infrared; chemické jevy; magnetická rezonanční tomografie; Magnetite Nanoparticles; fyzikální chemie; Dextrans; Culture Media; dextrany; kultivované buňky; nanočástice; Proteins; Ferrosoferric Oxide; Chemical Phenomena; endocytóza; polylysin; Mesenchymal Stem Cells; Cells, Cultured; proteiny; spektroskopie infračervená s Fourierovou transformací; molekulová hmotnost; kultivační média; Iron; Magnetics; oxid železnato-železitý; Endocytosis; krysa rodu Rattus; magnetismus; ultrazvuk; transmisní elektronová mikroskopie; zvířata; Molecular Weight; Polylysine; magnetické nanočástice; Rats; Ferric Compounds; adsorpce; Humans